Effects of Voriconazole on Cryptococcus neoformans - van Duin, David (American Society for Microbiology (ASM), 2004)
Voriconazole is a broad-spectrum triazole that offers extended activity against molds and yeasts that are not susceptible to earlier azole-type drugs. Recent studies indicate that melanization can severely reduce the susceptibility of certain antifungal drugs, but there is no information as to whether voriconazole is vulnerable to this effect. The activity of voriconazole on C. neoformans was assessed by MIC analysis and time-kill assays for melanized and nonmelanized cells. Cell morphology, capsule release, and phagocytosis of C. neoformans were studied in the presence or absence of subinhibitory concentrations of voriconazole. Voriconazole was fungicidal at concentrations of ≥8 μg/ml in vitro against the strains of C. neoformans examined, and its efficacy was not diminished by melanization. Cells grown in subinhibitory concentrations of voriconazole had smaller cellular and capsular volumes than cells grown in the absence of drug. The induction of the capsule by serum was not affected by voriconazole. Cells grown in subinhibitory concentrations of voriconazole released their capsule and were phagocytosed at rates comparable with yeast grown without the antifungal. The high activity of voriconazole against both melanized and nonmelanized cells results suggest that voriconazole may be a particularly valuable drug for cryptococcosis.